Valuation of Assets and Liabilities in Marshal’s Offices: Current Status and Prospects by the Integrated Reporting - Adamek-Hyska, Dorota; Wszelaki, Aneta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The article aims to analyse and evaluate the parameters of asset and liability valuation used in the marshal’s offices of local government units and evaluate how they are reported in terms of the developing idea of integrated reporting. In the empirical research, the authors drew attention to the orders of the voivodeship marshals on accounting policies and additional information from the marshal’s offices for the years 2020–2022. Directions for further research were also indicated.Research Design & Methods: A systematic literature review was used as the methodology. Literature studies were used to identify the current state of knowledge in the context of the problems studied. The Scopus and Web of Science databases were selected as data sources. The regulatory sphere concerning asset and liability valuation methods and reporting by local government budgetary units was analysed. In addition, a comparative and descriptive analysis of the collected empirical materials was carried out. A synthesis of the analysed results was created.Findings: The article presents the results of the analysis of accounting policies and additional information on Polish marshal’s offices in asset and liability valuation and assessment of their reporting in light of the developing idea of integrated reporting. This area is very sensitive because it should be disclosed every year in the first part of the additional information and thus published on the Public Information Bulletin (BIP) pages of these offices. Polish accounting law specifies the principles and methods of asset and liability valuation, leaving managers of accounting entities, including offices serving provincial and local government units, with many areas containing different possibilities for selecting valuation parameters.Implications / Recommendations: The considerations presented in the article indicate that the discretion allowed by the Polish accounting law directly shapes the property and financial image of the entity and its financial results, impacting the presentation of the entity’s performance. However, these entities’ selected models and methods of asset and liability valuation do not determine the direction of sustainable reporting because the accounting of typical public finance sector entities is mainly oriented toward fulfilling legal obligations for control and statistical purposes.Contribution: The issues that have been undertaken bridge the research and methodological gap in the studies on the possibility of sustainable reporting by marshal’s offices in Poland.